Citogenética de Santalales: Heterocromatina e Quantificação de DNA - Neves, Jose Achilles de Lima (2022)
Santalales is the largest order among the 12 orders of angiosperms with parasitic species, distributed in tropical and temperate regions, absent only in Antarctica. Ximeniaceae, Loranthaceae, Santalaceae and Viscaceae are four of the 20 families of the order Santalales, consisting of hemiparasitic plants with roots or branches and primary and/or secondary haustoria, characterized by presenting generally large chromosomes, stable chromosome numbers and large genomes. In this work we aim to: (1) Report numerical chromosome variation in representatives of Santalales, particularly Loranthaceae and Viscaceae, since cytological studies are mainly based on meiotic analyses; and (2) Understand the mechanisms acting in the karyotypic evolution of this hemiparasitic group of plants. For that, staining with DAPI was used, as well as the double CMA/DAPI and quantification of nuclear DNA through flow cytometry. All analyzed species presented reticulated interphase nuclei, with 2n = 16, 18 and 28 for Loranthaceae, 2n = 16 and 28 for Viscaceae, 2n = 28 for Santalaceae and 2n = 24 for Ximeniaceae. The largest chromosomes were observed for Phoradendron and Psittacanthus, and the smallest ones for Ximenia, Dendrophthoe and Santalum. CMA/DAPI banding technique revealed the presence of terminal CMA+ bands for Ximeniaceae, interstitial, subterminal and terminal CMA+ bands in Loranthaceae, while in representatives of Santalaceae and Viscaceae were observed interstitial and pericentromeric CMA+ bands. The size of the genomes varied eightfold in Loranthaceae and sevenfold in Viscaceae. Loranthaceae presented, on average, smaller genomes (2C = 54,62 pg) compared to Viscaceae (2C = 74,64 pg). The chromosome numbers of main genera in Loranthaceae and Viscaceae were numerically variable suggesting dysploidy and polyploidy events as important mechanisms on the evolution of these plant groups. Among the analyzed species of the order Santalales, it was not possible to correlate number, mean chromosome size and nuclear DNA content. As well as the frequency of polyploidy in Viscaceae and Santalaceae, a combined analysis of number, mean chromosome size and nuclear DNA content in the same populations is necessary. Obtain these data is particularly difficult due to technical problems related to chromosome analysis in plant members with parasitic habits.